Pengaruh Kepercayaan, Keamanan Transaksi, Harga, Kualitas Pelayanan, Dan Persepsi Akan Risiko Terhadap Keputusan Pembelian Pada Konsumen E-Commerce Shopee Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Metro - Widodo, Deny Edy; Ratmono, Ratmono; Mustakim, Rahmat (Jurnal Manajemen DIVERSIFIKASI, 2023)
The development and progress of information technology is currently growing very rapidlyand is very influential in everyday life, especially life in Indonesia. All of this can be seenfrom the large and large number of internet users in Indonesia, there must be a reason, oneof which is the development of infrastructure and the second is easy to get gadgets at lowprices. This study aims to 1) To find out whether there is an influence of trust on purchasingdecisions on Shopee E-commerce consumers on students at the University of Muhamadiyah Metro. 2) To find out whether there is a security effect on purchasing decisions on Shopee Ecommerce consumers at the University of Muhamadiyah Metro students. 3) To find outwhether there is an effect of price on purchasing decisions on Shopee E-commerceconsumers at the University of Muhamadiyah Metro students. 4) To find out whether there isan effect of service quality on purchasing decisions for E-commerce consumers throughShopee for students at the University of Muhammadiyah Metro. 5) To find out whether thereis an effect of perception of risk on purchasing decisions on Shopee E-commerce consumersfor students at the University of Muhammadiyah Metro. 6) To find out whether there is aneffect of trust, security, price, service quality, and perception of risk on purchasing decisionson Shopee E-commerce consumers at Muhamadiyah Metro University students... In thisstudy, the population was FEB students, Muhammadiyah University Metro Teknik samplingusing accidental sampling with a total sample of 72 people. Data collection techniques usinga questionnaire with a Likert scale. The results show that 1) there is a positive and significantinfluence between trust on purchasing decisions. 2) there is a positive and significantinfluence between security on purchasing decisions. 3) there is a positive and significanteffect of price on purchasing decisions 4) there is a positive and significant influence on thequality of service on purchasing decisions 5) there is a positive and significant influence onthe perception of risk on purchasing